The LUCID study: living with ulcerative colitis; identifying the socioeconomic burden in Europe - Leonardo Ruiz-Casas (BMC, 2021)
Abstract Background Ulcerative colitis (UC) is an inflammatory bowel disease with increasing prevalence worldwide. Current treatment strategies place considerable economic and humanistic burdens on patients. The aim of this study was to determine the socioeconomic burden of UC in adult patients in European countries in a real-world setting. Methods In this retrospective, cross-sectional and observational pan-European study, patients with moderate or severe UC were assigned to ARM 1 and patients who had moderate or severe UC but achieved mild or remission status 12 months before index date (or clinical consultation date), were assigned to ARM 2. Clinical and medical resource use data were collected via electronic case report forms, and data on non-medical and indirect costs, and health-related quality of life (HRQoL) were collected via patient and public involvement and engagement (PPIE) questionnaires. Per-patient annual total costs per ARM and per country were calculated using the collated resource use in the last 12 months (between the start of the documentation period and patient consultation or index date) and country specific unit costs. Quality of life was described by arm and by country. Results In the physician-reported eCRF population (n = 2966), the mean annual direct medical cost was €4065 in ARM 1 (n = 1835) and €2935 in ARM 2 (n = 1131). In the PPIE population (ARM 1, n = 1001; ARM 2, n = 647), mean annual direct cost was €4526 in ARM 1 and €3057 in ARM 2, mean annual direct non-medical cost was €1162 in ARM 1 and €1002 in ARM 2, mean annual indirect cost was €3098 in ARM 1 and €2309 ARM 2, and mean annual total cost was in €8787 in ARM 1 and €6368 in ARM 2. HRQoL scores showed moderate to high burden of UC in both groups. Conclusions The cost and HRQoL burden were high in patients in both ARM 1 and ARM 2 indicating unmet needs in the UC active population.